2009
DOI: 10.1029/2008gl035863
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric complexity or scale by scale simplicity?

Abstract: Is the numerical integration of nonlinear partial differential equations the only way to tackle atmospheric complexity? Or do cascade dynamics repeating scale after scale lead to simplicity? Using 1000 orbits of TRMM satellite radiances from 11 bands in the short wave (visible, infra red) long wave (passive microwave) and radar regions and 8.8 to 20,000 km in scale, we find that the radiance gradients follow the predictions of cascade theories to within about ±0.5%, ±1.25%, ±5.9% for the short waves, long wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…This accuracy is very close to those of the same moments of the visible and IR radiances over the range 10-5000 km (≈±0.5%, Lovejoy et al, 2009a).…”
Section: Testing Multiplicative Cascadessupporting
confidence: 58%
See 3 more Smart Citations
“…This accuracy is very close to those of the same moments of the visible and IR radiances over the range 10-5000 km (≈±0.5%, Lovejoy et al, 2009a).…”
Section: Testing Multiplicative Cascadessupporting
confidence: 58%
“…It is worth noting that the outer scales for these fields (∼8000-27 000 km) are approximately the same as the outer scales of the radiances (∼5000-32 000 km in Lovejoy et al, 2009a). We also mention that the C 1 's are not too different from the C 1 's for passive scalars (∼0.1) (Lilley et al, 2004).…”
Section: Testing Multiplicative Cascadesmentioning
confidence: 84%
See 2 more Smart Citations
“…There have been attempts to examine the scaling of model fields, both on a case-study basis as described above and more generally. Lovejoy et al (2009c) and Stolle et al (2009) concluded that weather could be modelled as a cascade process, pointing out that whereas horizontal scaling could be investigated for models with regularly spaced grids, the general absence of such regularity with altitude in atmospheric models used for assimilation and forecasting hampered analysis of their vertical scaling. In this case, the cascades refer to the meaning whereby the same processes are at work scale by scale across the whole scaling range…”
Section: Some Considerations For Numerical Modellingmentioning
confidence: 99%